Weekend light shifts evoke persistent Drosophila circadian neural network desynchrony - Nave, Ceazar; Roberts, Logan; Hwu, Patrick; Estrella, Jerson D; Vo, Thanh C; Nguyen, Thanh H; Pervolarakis, Nicholas; Shaw, Paul J; Leise, Tanya L; Holmes, Todd C (bioRxiv, 2020)
Billions of people subject themselves to phase-shifting light signals on a weekly basis by remaining active later at night and sleeping in later on weekends relative to weekday for up to a 3hr weekend light shift (WLS). Unnatural light signals disrupt circadian rhythms and physiology and behavior. Real-time light responses of mammalian suprachiasmatic nucleus are unmeasurable at single cell resolution. We compared Drosophila whole-circadian circuit responses between unshifted daytime/nighttime schedule and a 3hr WLS schedule at the single-cell resolution in cultured adult Drosophila brains using real-time bioluminescence imaging of the PERIOD protein for 11 days to determine how light shifts alter biological clock entrainment and stability. We find that circadian circuits show highly synchronous oscillations across all major circadian neuronal subgroups in unshifted light schedules. In contrast, circadian circuits exposed to a WLS schedule show significantly dampened oscillator synchrony and rhythmicity in most circadian neurons during, and after exposure. The WLS schedule first desynchronizes lateral ventral neuron (LNv) oscillations and the LNv are the last to resynchronize upon returning to a simulated weekday schedule. Surprisingly, one circadian subgroup, the dorsal neuron group-3 (DN3s), robustly increase their within-group synchrony in response to WLS exposure. Intact adult flies exposed to the WLS schedule show post-WLS transient defects in sleep stability, learning, and memory. Our findings suggest that WLS schedules disrupt circuit-wide circadian neuronal oscillator synchrony for much of the week, thus leading to observed behavioral defects in sleep, learning, and memory.